Risk Factors for Stress Fractures in Female Runners: Results of a Survey - Therese E Johnston; Allison E Jakavick; Caroline A Mancuso; Kathleen C McGee; Lily Wei; Morgan L Wright; Jeremy Close; Ayako Shimada; Benjamin E Leiby (North American Sports Medicine Institute, 2021)
# Background Few studies compare women with and without stress fractures and most focus on younger, elite runners. # Hypothesis/Purpose Compare risk factors between female runners with and without a stress fracture history. # Study Design Case control # Methods An online survey targeting women age ≥18 years was distributed primarily via social media. Questions included demographics, running details, cross training, nutrition, injury history, medical/menstrual history, and medications. Women with stress fracture histories answered questions about location, number, and changes made. Data were compared between groups using t-tests, chi-square tests, or Fisher's exact tests. Multivariable logistic regression models simultaneously investigated associations of multiple factors using backward variable selection. # Results Data from 1648 respondents were analyzed. Mean age was 40 years, and 25.4% reported stress fractures. Significant differences were found between groups for days/week running, mileage/week, running pace, years running, having a coach, cycling or swimming, calorie consumption for activity, other running injuries, medical history, medication/supplement intake, age at menarche, and going ≥6 months without a menstrual period. Odds of having a stress fracture were increased with osteopenia (OR 4.14), shin splints (OR 3.24), tendon injuries (OR 1.49), running >20 miles/week (OR 1.74-1.77) compared to 11-20 miles/week, having a coach (OR 1.86), and cycling (OR 1.15). Women running 11:00-11:59 minutes/mile or slower were less likely to have a stress fracture compared to those running 9:00-9:59 minutes/mile (OR 0.43-0.54). The odds of having a stress fracture were 1.43 times higher for going ≥ 6 months without a menstrual period. Use of calcium, probiotics, and vitamin D increased odds. Post fracture, common changes made were with cross training (49%), mileage (49%), and strength training (35%). # Conclusions Multiple intrinsic and extrinsic factors were identified for female runners who sustained one or more stress fracture during running. Prospective studies are warranted to infer a cause and effect relationship amongst these variables and stress fracture risk. # Level of Evidence Level IV